Optimization and characterization of green tea polyphenol extract from various solvents - Shabri Shabri; Dadan Rohdiana (Research Institute for Tea and Cinchona, 2016)
Tea has a high content of polyphenols with potent antioxidant activity and beneficial for health. Availability of polyphenols extract is still very limited. The aim of this study to optimation and characterization of green tea polyphenol extract base on some solvents. Parameters analyzed were polyphenol content and yield of some extraction process conditions. This result showed that extraction by the ratio of tea and solvent was 1 : 15 b/v, extracted by acetone 70% solution in temperature 600C for 15 minutes obtain polyphenol content of 53,30% b/b and total yield of 40,17% b/b.